Kumba Town N. A. Dog Licence Fees Order (Colonial Letters and the Contact of Knowledges, 1960)
This file contains colonial letters on Kumba Town N. A. Dog Licence Fees order
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Kumba; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies